UV Radiation Influence of Uranine Fluorescence in Water Samples - R. Kola, Liljana; B. Bylyku, Elida; Lazo, Pranvera (Asian Journal of Chemistry, 2010)
Fluorescence ability of uranine (fluorescence) enables its using as artificial tracer in the water system. Problem has to do with injection of uranine to trace and determine water movements within the karstic system and underground waters. Uranine has been used as an artificial tracer for the first times in Albania on 'Mali me Gropa' system study in year 2002. Fluorescence intensity (IF) of tracers in water samples depends on their physical and chemical properties, such as pH, temperature, presence of oxidants, etc. Besides that, UV radiation may induce photochemical decomposition of the dyes which can cause large measurement errors. This paper presents the influence of UV radiation on uranine fluorescence intensity in water samples in different conditions so-called: 'in light', 'in shadow', 'in colourless and brown glass bottle'. Concentration and synchronous scan methods were used for the measurement of uranine fluorescence by the means of a Perkin Elmer LS 55 luminescence spectrometer. Photodecomposition results help us to determine if the dye can be used or not in a water system study with tracing experiment. According to these results we can decide the conditions of the transport and storing of the water samples, too.